1989
DOI: 10.1007/bf00934128
|View full text |Cite
|
Sign up to set email alerts
|

Human early pregnancy factor: serum concentrations before and after therapeutic abortion in comparison with ?-hCG and an early pregnancy associated protein

Abstract: Serum concentrations of the early pregnancy factor (EPF), beta-hCG and the early pregnancy associated protein (EPAP) were measured in 12 patients before and after therapeutic abortion for social-medical reasons. Detection of EPF was performed by the rosette-inhibition assay, beta-hCG quantification by radioimmunoassay and EPAP measurements by rocket immunoelectrophoresis using a monospecific polyclonal rabbit antiserum. The disappearance rate of EPF after termination of pregnancy was closely correlated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Our results support the statements of Straube et al [ 18] and Hubei et al [8] and indicate that estimation of EPF could be of prognostic value in early pregnancy presenting with vaginal bleeding as suggested by Gerhard et al [19],…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Our results support the statements of Straube et al [ 18] and Hubei et al [8] and indicate that estimation of EPF could be of prognostic value in early pregnancy presenting with vaginal bleeding as suggested by Gerhard et al [19],…”
Section: Resultssupporting
confidence: 82%
“…Straube et al [ 18] have suggested that since EPF is the most sensitive parameter for the surveillance of early pregnancy, any disturbance of early pregnancy could be indicated by EPF estimations earlier than with commonly used hormones and sonographic determinations.…”
Section: Resultsmentioning
confidence: 99%
“…imminent abortion, missed abortion, ectopic pregnancy) show often a reduced serum EPF activity. Furthermore, after the death or loss of conceptus, EPF is no longer detectable in serum (Koch et al, 1982;Rolfe, 1982;Qin-Zheng, 1987;Sueoka et al, 1988;Straube et al, 1989). In human after therapeutic abortion, disappearance of EPF is indeed the earliest marker of embryonic loss (Mettler et al, 1985).…”
Section: Discussionmentioning
confidence: 99%